No detectable effect of ocean acidification on plankton metabolism in the NW oligotrophic Mediterranean Sea: Results from two mesocosm studies. (15th February 2017) - Maugendre, L.; Gattuso, J.-P.; Poulton, A.J.; Dellisanti, W.; Gaubert, M.; Guieu, C.; Gazeau, F.
Abstract: Oligotrophic areas account for about 30% of oceanic primary production and are projected to expand in a warm, high-CO2 world. Changes in primary production in these areas could have important impacts on future global carbon cycling. To assess the response of primary production and respiration of plankton communities to increasing partial pressure of CO2 ( p CO2 ) levels in Low Nutrient Low Chorophyll areas, two mesocosm experiments were conducted in the Bay of Calvi (Corsica, France) and in the Bay of Villefranche (France) in June–July 2012 and February–March 2013 under different trophic state, temperature and irradiance conditions. Nine mesocosms of 50 m 3 were deployed for 20 and 12 days, respectively, and were subjected to seven p CO2 levels (3 control and 6 elevated levels). The metabolism of the community was studied using several methods based on in situ incubations (oxygen light–dark, 18 O and 14 C uptake). Increasing p CO2 had no significant effect on gross primary production, net community production, particulate and dissolved carbon production, as well as on community respiration. These two mesocosm experiments, the first performed under maintained low nutrient and low chlorophyll, suggest that in large areas of the ocean, increasing p CO2 levels may not lead to a significant change in plankton metabolic rates and sea surface biological carbon fixation. Highlights: Two sites with different metabolic status. Summer conditions close to metabolic balance in the Bay of Calvi. Winter autotrophic conditions in the Bay of Villefranche, with no bloom. No effect of ocean acidification on plankton metabolic rates at both sites. Natural environmental limitations override a potential effect of ocean acidification.